Who is taking dietary supplements in Peru? Results of a non-probability cross-sectional survey - Palafox-Carlos, Hugo (2022)
Objective: To identify the profile and perception of dietary supplement users in the population of Lima, Arequipa and Trujillo, Peru. Materials and methods: An analytical cross-sectional study conducted with subjects over 18 years of age residing in the cities of Lima, Arequipa and Trujillo, Peru. The study was performed in two steps. In the first step, personal interviews were held using structured and standardized surveys. In the second step, a structured survey was designed with open and closed questions related to the purchasing and consumption habits of dietary supplements. Results: Eight hundred ninety (890) people were interviewed, out of which 42 % reported to be dietary supplement users, being vitamins and minerals the most commonly used products. It was observed that these users had been taking daily doses of dietary supplements for 3 to 12 months. Additionally, it was found that family and friends served as a source of information on dietary supplements similar to the one provided by doctors and nutritionists. Conclusions: The results of this study conducted with a representative sample from Lima, Arequipa and Trujillo showed that a high percentage of the population was satisfied with using dietary supplements regularly. It is important to point out that there were no significant differences between the percentage of the surveyed population that used dietary supplements recommended by nutritionists and the one which used them on family and friends’ recommendation. This suggests that it is necessary to improve nutritional habits with educational strategies on eating habits and adapt the use of dietary supplements to a balanced diet. These results could allow the population to use dietary supplements more effectively as a tool to reduce nutritional deficiencies.